G147 Randomized controlled trial comparing anticipated measles vaccination schedules to routine vaccination starting at 9 months in indian infants. (May 2019) - Makam, L; Mathew, J; Ratho, R; Dutta, S; Singh, M; Bharti, B; Suri, V; Massey, D
Abstract : Aim: Since 1985, Indian infants receive measles vaccine at 9 months of age. This age was chosen to balance the disappearance of maternal (transplacental) antibodies with the increasing risk of developing measles. However, 10%–15% measles infections may occur before the age of vaccination, necessitating earlier vaccination. This randomized controlled trial was designed to compare the safety and efficacy of anticipating measles vaccination in Indian infants. Methods: In this prospective, randomized controlled trial, infants were randomized at 6 months of age as follows: Group A: measles vaccination at 6 and 9 months; Group B: vaccination at 7.5 and 9 months; and Group C: vaccination at 9 months of age (current practice). IgG anti-measles antibody level (AMAL) was measured by ELISA just prior to vaccination and six weeks after each vaccination. The primary outcome was sero-protection defined as anti-measles antibody level >12 U/ml. Results: The proportion of susceptible infants in each group pre-vaccination was 95.2%, 100%, 97.1%, confirming the need for anticipating the vaccination schedule. Six weeks after vaccination, the proportion of protected infants was 23.8%, 57.8% and 71.4% in Groups A, B and C respectively (p<0.05 for comparison of Group A vs B and Group A vs C). An additional dose after the primary dose in Groups A and B resulted in 83.3% and 90.9% protected infants respectively at 1 year of age. No adverse events were noted after any of the vaccination doses. Conclusion: Anticipated vaccination is safe in infants. However, the efficacy is least for vaccination at 6 months and highest for at 9 months. Second dose of vaccine given at 9 months in first two groups resulted in sero-protection among 83.3% and 90.9% respectively. Infants who received a single dose of vaccine at 9 months of age are not fully protected and may require a closely spaced second dose of vaccine. This suggests that early vaccination should be followed by an additional dose of measles vaccine.